2058. Effect of Covid-19 lockdowns on identification of advanced HIV disease in outpatient clinics in Uganda. (15th December 2022) - Sekar, Preethiya; Nalintya, Elizabeth; Kavuma, Paul; Kigozi, Joanita; Ssuna, Martin; Kirumira, Paul; Naluyima, Rose; Namuli, Teopista; Skipper, Caleb; Hullsiek, Kathy Huppler; Boulware, David R; Meya, David; et al.
Abstract: Background: Despite HIV test and treat initiatives, the World Health Organization (WHO) estimates that 25% to 40% of persons living with HIV (PLWH) have advanced HIV disease (CD4< 200 cells/mcL). The objective of this study is to understand how the Covid-19 pandemic affected identification of persons with advanced HIV disease in Ugandan HIV clinics. Methods: We retrospectively reviewed data from 67 HIV clinics surrounding Kampala, Uganda. As part of routine data collection for PEPFAR reporting, number of persons entering care by clinic and number of persons presenting with CD4< 200 cells/mcL were summarized by month between July 2019 and January 2022. We used the Johns Hopkins Coronavirus Resource Center website to summarize Ugandan Covid-19 cases by month. Covid-19 lockdown dates were taken from the Ugandan government's COVID-19 information website. Specifically, between March and May 2020, there was a period of strict lockdown where public transportation was halted. Between May and July 2020 there was a less stringent lockdown (public transportation was available, but schools and many businesses remained closed). Again between June and July 2021 a strict lockdown occurred. Results: Prior to the Covid-19 pandemic, between July 2019 and February 2020, an average of 16% (265/1675) of PLWH presented monthly with advanced HIV disease. During Covid-19 lockdowns from March 2020 to July 2020, only 9% (102/1124) of PLWH presented with advanced HIV disease. During the period of lockdown, there was a 33% reduction in the monthly average number of PLWH presenting to HIV clinics, and a 62% reduction in the monthly average number of PLWH presenting with advanced HIV disease. From February 2021 to January 2022, 18% (185/987) of PLWH presented with advanced HIV disease. During this period, there was a 42% reduction in the number of persons presenting to HIV care; of those who presented, a larger portion presented with advanced HIV disease. Conclusion: The Covid-19 lockdowns negatively affected presentation of PLWH to care, most significantly among persons with advanced HIV disease. This reduction in presentation to care has persisted and not recovered to pre-Covid levels. In the past year, 18% of PLWH presented with advanced HIV disease. Disclosures: All Authors : No reported disclosures.